Cover Image, Volume 39, Issue 3. Issue 3 (8th February 2018) - Abbott, Jamie A.; Meyer‐Schuman, Rebecca; Lupo, Vincenzo; Feely, Shawna; Mademan, Inès; Oprescu, Stephanie N.; Griffin, Laurie B.; Alberti, M. Antonia; Casasnovas, Carlos; Aharoni, Sharon; Basel‐Vanagaite, Lina; Züchner, Stephan; et al.
Abstract : On the cover : This cover image, by Jamie A. Abbott et al., is based on the Research Article Substrate interaction defects in histidyl‐tRNA synthetase linked to dominant axonal peripheral neuropathy, Pages 415‐432. DOI:10.1002/humu.23380 .